2019
DOI: 10.1002/app.48406
|View full text |Cite
|
Sign up to set email alerts
|

Functionality of chitosan‐halloysite nanocomposite films for sustained delivery of antibiotics: The effect of chitosan molar mass

Abstract: This study was designed to investigate functionality of tetracycline‐loaded chitosan‐halloysite nanocomposite films, with focus on evaluating the influence of chitosan molar mass on films applicability for sustained local antibiotic delivery. The films were prepared by casting and solvent evaporation using low, medium, and high molar mass chitosan. SEM analysis revealed compact, nonporous and rough surface of the nanocomposite films due to the presence of halloysite agglomerates and tetracycline crystals. Incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…To the light of these aspects, thermo-responsive nanocarriers were prepared by the functionalization of HNTs with charged PNIPAAMs for the controlled delivery of drugs into biological systems [48]. Additionally, the design of new hybrid and biohybrid materials was carried out using drug-loaded halloysite for health applications as antimicrobial patches or anti-inflammatory drugs-releasing tablets [49][50][51][52]. Similarly, the nanotubes were used for the encapsulation of corrosion inhibitors with the aim to coat and protect metal surfaces [53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…To the light of these aspects, thermo-responsive nanocarriers were prepared by the functionalization of HNTs with charged PNIPAAMs for the controlled delivery of drugs into biological systems [48]. Additionally, the design of new hybrid and biohybrid materials was carried out using drug-loaded halloysite for health applications as antimicrobial patches or anti-inflammatory drugs-releasing tablets [49][50][51][52]. Similarly, the nanotubes were used for the encapsulation of corrosion inhibitors with the aim to coat and protect metal surfaces [53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…For the SC ( Figure 1 a), the absorption peaks at 1034 cm −1 , 791 cm −1 , 695 cm −1 , 538 cm −1 , 469 cm −1 were attributed to the Si–O, Si–O–Si and Si–O–Al, respectively. More importantly, the peaks at 1100 cm −1 , 3694 cm −1 and 3619 cm −1 assigned to the stretching vibration of the apical Si–O group, as well as the stretching vibration of O-H in kaolinite [ 13 , 27 ], suggested the SC contained the silicate mineral of kaolinite. The XRD characterization also verified the kaolinite of in SC ( Figure S1, Supplementary Material ).…”
Section: Resultsmentioning
confidence: 99%
“…A large number of researches have indicated that the introduction of a certain amount of inorganic substances into the polymeric structure of superabsorbent hydrogels cannot only significantly increase its water absorption rate, but also effectively reduce the product cost. Therefore, the superabsorbent composites, which incorporate the inorganic materials including silicate mineral and metallic ions such as attapulgite [11,12], kaolinite [13,14], bentonite [15,16], titanium dioxide [17,18], zinc oxide, and aluminum ions [19] into the superabsorbent composites have attracted researchers' widespread attention. Factory (Shanghai, China); other chemical reagents were all analytical grade and utilized as obtained without further purification.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous antibacterial compounds were loaded into the HNTs, such as antibiotics, [108][109][110][111][112][113] disinfectants, 114,115 essential oils, [116][117][118][119] and antimicrobial peptides. 120 For example, loading of the disinfectant chlorhexidine gluconate resulted in a sustained release rate, three times slower than the free compound.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…93,107 The loaded HNTs are introduced either during the polymerization process, 113 or dispersed within a polymer melt [116][117][118][119] or solution. 108,124 The resulting polymer/ HNTs nanocomposites can be used in many formats, including active films, [116][117][118][119] electrospun substrates, 125,126 membranes, 124 dental coatings, [127][128][129] and bone cement. 113,130 In some cases, the addition of HNTs into the matrix not only slows down the release rate of the antimicrobial compound, but also improves the physical properties of the resulting nanocomposites.…”
Section: Antibacterial Activitymentioning
confidence: 99%